Viscid globules in webs of the spider achaearanea tesselata (araneae: theridiidae) - Barrantes Montero, Gilbert (2006)
We describe the presence and dimensions of viscid globules in both the sheet and tangle portions of the webs of Achaearanea tesselata (Keyserling 1884). We found viscid globules in all sheets and tangles of the webs examined. The globules were very small and water soluble. The globules were present in the sheet of the first web built by a juvenile (n 1), but their density was lower than in webs of mature females (n 6).